Factors associated with success or failure of quit attempts: a clinical approach for lung cancer prevention - Tin, Tin Su; Sallehuddin, B.A.B.; Murniati, H.H.; Swinder, J.; Al Sadat, N.; Saimy, I. (West Asia Organization for Cancer Prevention, 2012)
The objective of the study is to investigate the success rate of quit attempts and identify factors associated with success or failure of quit attempts in a quit smoking clinic. A cohort study was conducted with 495 smokers who enrolled in a quit smoking clinic from 2005 to 2008. The factors leading to quit smoking successfully were "being Malay", "having high blood pressure" "type of Nicotine Replacement Therapy" and "duration of follow up". In contrast, clerical staff had negative association to quit smoking. People who started smoking in their teenage years had a high risk of relapse. Integration of active follow up and tailor-made support programmes for quitters appear necessary in order to maintain their non-smoking status and encourage them to be permanent quitters. Integration of quit smoking clinics and primary care clinics could be another potential step for the success of quit smoking programmes.